Regional Government as the Main Element of Non-Military Defense to Support National Defense - Susilawati, Susilawati; Supriyadi, A. A. (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
The decentralized government system in Indonesia divides authority between the central and regional governments according to the characteristics of the vast archipelagic region. The main priority in this system is ensuring the fulfillment of basic needs such as security, health, education, justice and welfare, as reflected in the national goals stated in the 1945 Constitution. The state plays the role of guardian and protector for the people, with the government's focus on creating order in social life. . Efforts focused on national defense aim to defend the sovereignty, integrity and safety of the nation from various threats, both domestic and international. Indonesia's national defense posture consists of military defense to face military threats and non-military defense to face non-military threats, which are expected to achieve national goals. In the context of the dynamics of life that continue to develop, the role of regional government as the main element in non-military defense is important, because it has direct contact with the community to build local wisdom in advancing its region. By building a non-military defense posture as an integral part of regional government, regions will become stronger in supporting the performance of the central government and become an efficient and effective unit in achieving national goals.